Pembelajaran Komunikasi Matematika dalam Think Pair Share - Nasution, Mariyam (IAIN PADANGSIDIMPUAN, 2013)
ability [of] Communications matematik [is] one of [the] elementary ability [of] study [of] mathematics in reading, comprehending, explaining, and expressing a[n problem of to matematik. One of [the] study model able to develop ability [of] educative [by] participant matematik communications [is] model study [of] Think Pair Share ( TPS). Model this study put in the way of educative participant to work [by] xself and also cooperate with others so that can improve ability [of] matematik communications learnt and cooperate to solve problems.Writer here aim to to study usage model study [of] Think Pair Share type co-operative ( TPS) to ability [of] educative participant matematik communications in study [of] matematik and know educative participant respon to model study [of] Think Pair Share type co-operative ( TPS).